Transepithelial sodium transport and carbon dioxide production by the toad urinary bladder in the absence of serosal sodium. - Macknight, A D (1977)
1. The production of CO2 in relation to sodium transport by toad urinary bladder has been examined in the absence of sodium from the serosal medium. 2. Replacement of serosal sodium by choline increased CO2 production without stimulating short-circuit current. Replacement of serosal medium by Tris did not have this effect. 3. With serosal sodium Ringer replaced by Tris Ringer, the ratio of sodium transported to CO2 produced was not altered significantly. 4. The results therefore suggest that there is no important recycling of sodium between the serosal medium and the transporting epithelial cells.